Combined basilar subsegmentectomy for intralobar sequestration via uniportal VATS: a case report - Satoshi Takamori; Hiroyuki Oizumi; Jun Suzuki; Satoshi Shiono (Surgical Case Reports)
Abstract Background Combined basilar subsegmentectomy via uniportal video-assisted thoracoscopic surgery is an extremely complex surgery. Moreover, no the existing reports describe the procedure and technique. Here, we present the technique of combined basilar subsegmentectomy that was successfully performed via uniportal video-assisted thoracoscopic surgery to treat intralobar pulmonary sequestration in an adult patient. Case presentation A 57-year-old man underwent surgery for oropharyngeal carcinoma. Preoperative computed tomography showed several cystic lesions in the right lower lobe. Subsequent enhanced computed tomography revealed an anomalous artery branching from the abdominal aorta and a normal pulmonary vein. The patient with diagnosed with Pryce type III intralobar pulmonary sequestration and underwent right S7 posterior + 10bc combined basilar segmentectomy via uniportal video-assisted thoracoscopic surgery. The postoperative course was uneventful, and the patient was discharged 4 days after surgery. At the 8-month follow-up, computed tomography showed no abnormalities. Conclusions We successfully performed combined basilar subsegmentectomy via uniportal video-assisted thoracoscopic surgery. This surgical approach is useful for the treatment of intralobar pulmonary sequestration occurring at the basal segment of the lung.